Working memory capacity and the risky-choice framing effect: A preregistered replication and extension of Corbin et al. () - Bogdanov, Boris; Corbin, Jonathan; Dobreva, Sabina; McElroy, Todd; Rachev, Nikolay R. (Judgment and decision making, 2023)
While working memory capacity is associated with superior performance on a number of tasks, could it paradoxically sometimes be associated with suboptimal performance? Corbin et al. (2010, Judgment and Decision Making 5(2), 110–115) found that, in a between-subjects design, higher WMC is associated with a larger risky-choice framing effect, traditionally conceived of as a departure from rational principles. Such surprising findings are of potentially great theoretical importance; yet the original study was underpowered. In this registered report, we aimed to replicate and extend the original findings, by conducting an online experiment among 425 North Americans. To extend the findings beyond the specific single tasks used in the original study, we used three WMC tasks with different processing components and six framing problems involving human lives. In a close replication, the frame significantly interacted with neither the Ospan short absolute score nor the Ospan short partial score in predicting ratings on the disease-framing problem. Similarly, in an extended replication, a composite WMC score did not significantly interact with the frame in predicting ratings on three framing problems involving human lives. The Bayes factors showed that the data were 3 to 10 times more likely under the null hypothesis of no interaction between WMC and frame. Taken together, these findings show an absence of association between the between-subjects risky-choice framing effect and WMC. This outcome is compatible with four out of the six theoretical accounts we considered, and is uniquely predicted by the default-interventionist dual-process account and the pragmatic inference account. Further research can more rigorously pit conflicting predictions of these accounts against each other.